STRATEGI BISNIS TOKO PERSATUAN - Kundala, Manendha Maganitri (PRIMA EKONOMIKA, 2019)
ABSTRACT The development of the Indonesian economy as a whole after the monetary crisis showed a significant increase, this is shown by the start of the rise of various trading businesses in the community. One such business is the school supplies business. School equipment is a mandatory attribute used by all children who have received formal education in Indonesia. As the business world develops, the school supplies business is no exception, more and more new players will emerge in this business. Increasing the number of business players means increasing the intensity of competition. Because of that condition, the Unity Store must find the right business strategy to win the competition. The Unity Shop is demanded to be able to maximize its strengths to take advantage of existing opportunities and minimize its weaknesses to overcome existing threats. This study uses a SWOT-4K analysis that begins by listing the strengths, weaknesses, opportunities and business threats faced by the Unity Stores. All indicators are calculated for their weighted values ​​after giving weight and values ​​for each indicator. The combination of the weighted values ​​of internal and external variables is what determines the choice of strategy that is considered appropriate for the Union Store. The high intensity of competition is very influential for the Unity Store. But the Union Shop is required to continue to survive. The results of the SWOT-4K study show the Unity Store should use a growth strategy. The combination of market development strategies, market penetration strategies, and product development strategies is an appropriate growth strategy for the Unity Store. Keywords: Internal environment analysis, external environment analysis, SWOT-4K analysis, growth strategy. ABSTRAK Perkembangan perekonomian Indonesia secara keseluruhan pasca krisis moneter menunjukkan peningkatan yang cukup berarti, hal ini ditunjukkan oleh mulai maraknya berbagai bisnis-bisnis perdagangan di masyarakat. Salah satu bisnis tersebut adalah bisnis perlengkapan sekolah. Perlengkapan sekolah merupakan atribut wajib yang dipakai oleh semua anak yang mengenyam pendidikan formal di Indonesia. Seiring perkembangan dunia bisnis, tak terkecuali bisnis perlengkapan sekolah, maka akan semakin banyak muncul pemain baru di bisnis ini. Makin banyaknya jumlah pemain bisnis berarti semakin meningkatkan intensitas persaingannya. Karena keadaan itulah Toko Persatuan harus mencari strategi bisnis yang tepat untuk bisa memenangkan persaingan. Toko Persatuan dituntut untuk bisa memaksimalkan kekuatan untuk memanfaatkankan peluang yang ada dan meminimalkan kelemahannya untuk mengatasi ancaman yang ada. Penelitian ini menggunakan analisis SWOT-4K yang dimulai dengan membuat daftar indikator kekuatan, kelemahan, peluang, dan ancaman bisnis yang dihadapi oleh Toko Persatuan. Semua indikator dihitung nilai tertimbangnya setelah sebelumnya diberkan bobot dan nilai untuk masing-masing indikator. Kombinasi nilai tertimbang variabel internal dan eksternal tersebut yang menjadi penentu pilihan strategi yang dianggap pas untuk Toko Persatuan. Intensitas persaingan yang tinggi sangatlah berpengaruh bagi Toko Persatuan. Namun Toko Persatuan dituntut untuk terus bertahan. Hasil penelitian SWOT-4K menunjukkan Toko Persatuan selayaknya menggunakan strategi pertumbuhan. Kombinasi dari strategi pengembangan pasar, strategi penetrasi pasar, dan strategi pengembangan produk merupakan strategi pertumbuhan yang pas untuk Toko Persatuan. Kata kunci : Analisis lingkungan internal, analisis lingkungan eksternal, analisis SWOT-4K, strategi pertumbuhan.